Associations between light at night and mental health: A systematic review and meta-analysis - Andy Deprato; Prasun Haldar; José Francisco Navarro; Barbara N. Harding; Paige Lacy; Robert Maidstone; Saibal Moitra; Anna Palomar-Cros; Hannah Durrington; Manolis Kogevinas; Subhabrata Moitra; Ana Adan (Science of The Total Environment, 2025)

Indoor and outdoor artificial light-at-night (ALAN) and cancer risk: A systematic review and meta-analysis of multiple cancer sites and with a critical appraisal of exposure assessment - Anna Palomar-Cros; Andy Deprato; Kyriaki Papantoniou; Kurt Straif; Paige Lacy; Robert Maidstone; Ana Adan; Prasun Haldar; Saibal Moitra; José Francisco Navarro; Hannah Durrington; Subhabrata Moitra; et al. (Science of The Total Environment, 2024)

Generation and characterisation of scalable and stable human pluripotent stem cell-derived microvascular-like endothelial cells for cardiac applications - Qasim A. Majid; Bishwa R. Ghimire; Bela Merkely; Anna M. Randi; Sian E. Harding; Virpi Talman; Gábor Földes (Angiogenesis, 2024)
Coronary microvascular disease (CMD) and its progression towards major adverse coronary events pose a significant health challenge. Accurate in vitro investigation of CMD requires a robust cell model that faithfully represents the cells within the cardiac microvasculature. Human pluripotent stem cell-derived endothelial cells (hPSC-ECs) offer great potential; however, they are traditionally derived via differentiation protocols that are not readily scalable and are not specified towards the microvasculature. Here, we report the development and comprehensive characterisation of a scalable 3D protocol enabling the generation of phenotypically stable cardiac hPSC-microvascular-like ECs (hPSC-CMVECs) and cardiac pericyte-like cells. These were derived by growing vascular organoids within 3D stirred tank bioreactors and subjecting the emerging 3D hPSC-ECs to high-concentration VEGF-A treatment (3DV). Not only did this promote phenotypic stability of the 3DV hPSC-ECs; single cell-RNA sequencing (scRNA-seq) revealed the pronounced expression of cardiac endothelial- and microvascular-associated genes. Further, the generated mural cells attained from the vascular organoid exhibited markers characteristic of cardiac pericytes. Thus, we present a suitable cell model for investigating the cardiac microvasculature as well as the endothelial-dependent and -independent mechanisms of CMD. Moreover, owing to their phenotypic stability, cardiac specificity, and high angiogenic potential, the cells described within would also be well suited for cardiac tissue engineering applications.

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

Active breeding seabirds prospect alternative breeding colonies - Jelena Kralj; Aurore Ponchon; Daniel Oro; Barbara Amadesi; Juan Arizaga; Nicola Baccetti; Thierry Boulinier; Jacopo G. Cecere; Robin M. Corcoran; Anna-Marie Corman; Leonie Enners; Abram Fleishman; et al. (Oecologia, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Selenium: Mercury Molar Ratios in Freshwater Fish in the Columbia River Basin: Potential Applications for Specific Fish Consumption Advisories - Leanne K Cusack; Collin Eagles-Smith; Anna K Harding; Molly Kile; Dave Stone (Biological Trace Element Research, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Limited use of sea ice by the Ross seal (Ommatophoca rossii), in Amundsen Sea, Antarctica, using telemetry and remote sensing data - Anna Arcalís-Planas; Signe Sveegaard; Olle Karlsson; Karin C. Harding; Anna Wåhlin; Tero Harkonen; Jonas Teilmann (Polar Biology, 2015)

Naphthalene Biomarkers and Relationship with Hemoglobin and Hematocrit in White, Black, and Hispanic Adults: Results from the 2003–2004 National Health and Nutrition Examination Survey - Daniel L. Sudakin; Ellen Smit; Andres Cardenas; Anna Harding (Journal of Medical Toxicology, 2013)

Modelling the potential impact of global warming on Ips typographus voltinism and reproductive diapause - Anna Maria Jönsson; Susanne Harding; Paal Krokene; Holger Lange; Åke Lindelöw; Bjørn Økland; Hans Peter Ravn; Leif Martin Schroeder (Climatic Change, 2011)

Spatio‐temporal impact of climate change on the activity and voltinism of the spruce bark beetle, Ips typographus - ANNA MARIA JÖNSSON; GUSTAF APPELBERG; SUSANNE HARDING; LARS BÄRRING (Global Change Biology, 2009)
The spruce bark beetle Ips typographus is one of the major insect pests of mature Norway spruce forests. In this study, a model describing the temperature‐dependent thresholds for swarming activity and temperature requirement for development from egg to adult was driven by transient regional climate scenario data for Sweden, covering the period of 1961–2100 for three future climate change scenarios (SRES A2, A1B and B2). During the 20th century, the weather supported the production of one bark beetle generation per year, except in the north‐western mountainous parts of Sweden where the climate conditions were too harsh. A warmer climate may sustain a viable population also in the mountainous part; however, the distributional range of I. typographus may be restricted by the migration speed of Norway spruce. Modelling suggests that an earlier timing of spring swarming and fulfilled development of the first generation will significantly increase the frequency of summer swarming. Model calculations suggest that the spruce bark beetle will be able to initiate a second generation in South Sweden during 50% of the years around the mid century. By the end of the century, when temperatures during the bark beetle activity period are projected to have increased by 2.4–3.8 °C, a second generation will be initiated in South Sweden in 63–81% of the years. The corresponding figures are 16–33% for Mid Sweden, and 1–6% for North Sweden. During the next decades, one to two generations per year are predicted in response to temperature, and the northern distribution limit for the second generation will vary. Our study addresses questions applicable to sustainable forest management, suggesting that adequate countermeasures require monitoring of regional differences in timing of swarming and development of I. typographus , and planning of control operations during summer periods with large populations of bark beetles.

Evaluating Microbial Indicators of Environmental Condition in Oregon Rivers - ALAN T. PENNINGTON; ANNA K. HARDING; CHARLES W. HENDRICKS; HEIDI M. K. CAMPBELL (Environmental Management, 2001)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)